APPLICATION OF HEURISTIC ALGORITHMS IN LOGISTICS - Bogdanov, Andrey (Journal Scientific and Applied Research, 2024)
The paper deals with algorithms for solving logistics problems. It describes types of heuristic algorithms focusing on their strengths and weaknesses. Incorporating the advantages and disadvantages of heuristic algorithms, it offers feasible solutions.